2022
DOI: 10.3390/metabo12020179
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Analysis of Male Patients with Cannabis or Amphetamine Use Disorder

Abstract: Studies have demonstrated that chronic consumption of abused drugs induces alterations in several proteins that regulate metabolism. For instance, methamphetamine exposure reduces glucose levels. Fatty and amino acid levels were altered in groups exposed to abused drugs. Therefore, in our study, we investigated the serum metabolomic profile of patients diagnosed with cannabis and/or amphetamine use disorders. Blood was obtained from subjects (control, amphetamine, and cannabis). Detection of serum metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…However, it is possible that altered levels of acylcarnitines are caused by cannabis use per se. Hexanoylcarnitine had a direct positive association with cannabis use in this sample (Supplementary Table 4), and cannabis use has previously been suggested to alter carnitine synthesis pathways (Alasmari et al, 2022). Cannabinoid effects on cellular energy metabolism have previously been reported (Farokhnia et al, 2020).…”
Section: Alterations Related To Cannabis Usesupporting
confidence: 51%
See 1 more Smart Citation
“…However, it is possible that altered levels of acylcarnitines are caused by cannabis use per se. Hexanoylcarnitine had a direct positive association with cannabis use in this sample (Supplementary Table 4), and cannabis use has previously been suggested to alter carnitine synthesis pathways (Alasmari et al, 2022). Cannabinoid effects on cellular energy metabolism have previously been reported (Farokhnia et al, 2020).…”
Section: Alterations Related To Cannabis Usesupporting
confidence: 51%
“…On the contrary, low valine levels have been reported in rst-episode psychotic patients (Leppik et al, 2018). However, a positive association between cannabis use and serum valine levels has also been reported (Alasmari et al, 2022), suggesting that high valine levels could be associated with cannabis use.…”
Section: Alterations Related To Cannabis Usementioning
confidence: 99%
“…By inhibiting mitochondrial metabolism [111,112,[164][165][166][167][168][169][170], cannabinoids interfere with the supply of substrates to the epigenomic machinery and the supply of energy for both genomic and epigenomic maintenance. Due to mitochondrial inhibition, the cellular levels of lactate rises [171][172][173][174][175] which induces both passive and enzymically mediated lactylation of key metabolic enzymes [176,177]. This further reinforces the increase in cellular dependence on glycolysis and a stem-like cellular de-differentiated state and locks cells into a premalignant metabolomic-epigenomic state [176][177][178][179].…”
Section: Mechanisms 441 Epigenomicsmentioning
confidence: 93%
“…Important medications with stimulant and anxiolytic properties frequently are misused or overused, which has been linked to serious side effects, and higher mortality and morbidity rates around the world, and severe side effects. Cannabis and amphetamine are two narcotics that are frequently combined, and addiction to both drugs has risen globally, especially in Saudi Arabia 2 . In addition, a study in Jazan, Saudi Arabia found that the number of fatalities related to amphetamine addiction and other narcotics substances increased from 18 to 80% between 2018 and 2020 3 , but in the Qassim region, cannabis addiction was the most prevalent drug usage, followed by amphetamine 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis and amphetamine are two narcotics that are frequently combined, and addiction to both drugs has risen globally, especially in Saudi Arabia 2 . In addition, a study in Jazan, Saudi Arabia found that the number of fatalities related to amphetamine addiction and other narcotics substances increased from 18 to 80% between 2018 and 2020 3 , but in the Qassim region, cannabis addiction was the most prevalent drug usage, followed by amphetamine 2 .…”
Section: Introductionmentioning
confidence: 99%